Incorporation of mineral nitrogen into the soil food web as affected by plant community composition - Strecker, Tanja (Ecol Evol, 2021)
Although nitrogen (N) deposition is increasing globally, N availability still limits many organisms, such as microorganisms and mesofauna. However, little is known to which extent soil organisms rely on mineral‐derived N and whether plant community composition modifies its incorporation into soil food webs. More diverse plant communities more effectively compete with microorganisms for mineral N likely reducing the incorporation of mineral‐derived N into soil food webs. We set up a field experiment in experimental grasslands with different levels of plant species and functional group richness. We labeled soil with (15)NH(4) (15)NO(3) and analyzed the incorporation of mineral‐derived (15)N into soil microorganisms and mesofauna over 3 months. Mineral‐derived N incorporation decreased over time in all investigated organisms. Plant species richness and presence of legumes reduced the uptake of mineral‐derived N into microorganisms. In parallel, the incorporation of mineral‐derived (15)N into mesofauna species declined with time and decreased with increasing plant species richness in the secondary decomposer springtail Ceratophysella sp. Effects of both plant species richness and functional group richness on other mesofauna species varied with time. The presence of grasses increased the (15)N incorporation into Ceratophysella sp., but decreased it in the primary decomposer oribatid mite Tectocepheus velatus sarekensis. The results highlight that mineral N is quickly channeled into soil animal food webs via microorganisms irrespective of plant diversity. The amount of mineral‐derived N incorporated into soil animals, and the plant community properties affecting this incorporation, differed markedly between soil animal taxa, reflecting species‐specific use of food resources. Our results highlight that plant diversity and community composition alter the competition for N in soil and change the transfer of N across trophic levels in soil food webs, potentially leading to changes in soil animal population dynamics and community composition. Sustaining high plant diversity may buffer detrimental effects of elevated N deposition on soil biota.